Novel approaches to reduce the risk of falling in community dwellings: effects of two multimodal programs in lower-body strength—a pilot study. (3rd August 2021) - Rosado, H; Bravo, J; Raimundo, A; Carvalho, J; Leite, N; Pereira, C
Abstract: Background: Muscle weakness is a key risk factor for falls and strength exercises should be included in fall prevention programs. A psychomotor intervention promoting motor stimulation and the whole-body vibration (WBV) providing muscle contractions may reduce the incidence of falls. Our hypothesis relies on the greater benefits of a combined program. This study aimed to evaluate the effectiveness and the feasibility of two 12-week multimodal programs in lower-body strength in community dwellings fallers or with balance impairment. Methods: Thirty-seven participants (34 women; mean age 74.3 ± 5.2 years) were allocated into: experimental group 1 [EG1] (psychomotor intervention), or experimental group 2 [EG2] (combined program: psychomotor intervention plus WBV), 3x/week. Maximal strength of knee extensors and flexors was assessed by an isokinetic dynamometer at 60°/s. Wilcoxon and Mann-Whitney tests were performed. Results: The overall adherence rate was high (86.3%), with a level intensity in the rating of perceived exertion of 12.1 ± 0.3 points, in EG1, and 12.5 ± 0.4 points, in EG2. Significant changes between the pre-post intervention were observed exclusively in EG2, in the variables 'Peak torque extension' (71.7 ± 28.6 Nm vs. 79.2 ± 23.5 Nm, P = 0.042) and 'Agonist/Antagonist ratio' (60.2 ± 13.0 vs. 53.5 ± 8.6, P = 0.013). The effect size ( r ) in both variables was medium. No significant changes between groups were detected. Conclusions: This pilot results indicate that both programs were feasible and well-tolerated. The combined program demonstrates larger effectiveness, since the WBV may positively influence the lower-body strength, reducing the risk of falls. Trial Registration: ClinicalTrials.gov Identifier: NCT03446352. Funding: This pilot was granted by the ESACA Project (Grant ALT20-03-0145-FEDER-000007) and by FCT (SFRH/BD/147398/2019).